(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to determine the effect of storage conditions on the quality of pasteurized milk distributed in Khartoum North by three companies. Sixty samples were collected from the product of each company and subjected to chemical analysis and microbiological examination in the third and fifth day of processing. The results revealed significant (P<0.05) differences between the products of the three companies in fat, solids not fat, density, protein and lactose. Microbiological analysis showed that total bacterial count, coliform count and aerobic spore formers count were significantly (P<0.05) affected by the sources of samples and storage period. The present study concluded that the quality of pasteurized milk produced by the three dairy companies was low. 0Therefore, development of programs of health and quality of dairy products are urgently needed to ensure that good quality pasteurized milk is produced and consumed in Khartoum State.